Lessons for South Africa: China during the era of ‘reform and opening up’ - Scott, Douglas (New Agenda: SA Journal of Social and Economic Policy, 2024)
China's economic rise may now be slowing down, but the lessons for South Africa, grappling with its own stubborn development challenges, remain important. While Beijing currently navigates potential stagnation after four decades of breakneck speed economic development, its "reform and opening up" era offers valuable insights for Pretoria. This article argues that South Africa should re-orientate its relationship with China so as to better learn from, and recreate, the successes of China’s development experience. To do this requires appreciating what those successes are and where, as well as which lessons are not worth repeating on South Africa’s own development path.